The Succession Patterns of Agricultural Lands in the Special Region of Yogyakarta Province, Indonesia - Maulida, Yuhan Farah; Wati, Ratih Ineke; Subejo, Subejo (Mahidol University, Institute for Population and Social Research, 2022)
With prolonged agriculture population aging, farmer regeneration has posed a widespread challenge for developing global agrarian communities. In Indonesia, the younger generation’s disinterest in working in agriculture has evolved into a significant obstacle in the succession process. The study investigates the patterns, challenges, and strategies for farmer regeneration in the Special Region of Yogyakarta province. The analysis used a qualitative case study with data collection techniques through focus group discussions, interviews, and observations. Respondents are 33 experienced older and younger farmers residing in three distinctly allocated research locations in Yogyakarta, namely Sleman, Kulon Progo, and Gunung Kidul regions. The results demonstrate that the younger generation’s career choices vary by rural-urban spatial differences. The study revealed different arrangements in the land inheritance system but no significant variance in the time when the succession happened. The geographical context, land conversion, socialization of the profession, and growing non-farm opportunities are inter-linked as the cognitive factors in farm continuation across generations. To procure an efficient succession process, the research established the implementation of determinants such as improved socialization, recognition of young farmers as innovators, promotion of agricultural-related educational opportunities, and strengthening incentives. © 2022